Adapted Acoustic CR Neuromodulation in Patients With Chronic Tonal Tinnitus and Hearing Loss - Wurzer, Hannes; Hauptmann, Christian (Frontiers in Medicine, 2018)
Chronic tonal tinnitus is often accompanied by sensorineural hearing loss which is associated with altered tuning curves and bandwidth of alternating masking. In this feasibility study the so-called hearing threshold adapted coordinated reset (HTA-CR) neuromodulation was investigated. This method is based on CR neuromodulation, which has been demonstrated to be an effective treatment for chronic tonal tinnitus. It applies four stimulation tones that are determined by the patient's individual tinnitus frequency and hearing impairment. The HTA-CR neuromodulation was programmed to the Desyncra™ for Tinnitus Therapy System and treatment was applied to 25 patients for 4 months on average and 4 h daily. Regular check-ups were done every 4–6 weeks. Therapy outcome was assessed by the tinnitus questionnaire (Tinnitusfragebogen, TF) as per Goebel and Hiller. After 4 months the mean TF score was reduced by 27.4%. A reduction of ≥ 15 points was found in 40% of the patients while for further 32% of the patients a reduction of 6–14 points was found. Thus, a positive response rate of 72% was observed after 4 months of HTA-CR neuromodulation. Our results suggest that HTA-CR neuromodulation might be at least comparable to standard CR neuromodulation providing another effective therapeutic option for the treatment of chronic tonal tinnitus.